Regulation of Adenosine 3′:5′-Cyclic Monophosphate Phosphodiesterase Activity in Fibroblasts by Intracellular Concentrations of Cyclic Adenosine Monophosphate - D'Armiento, Massimo (1972)
Cyclic AMP-phosphodiesterase is present in various mouse fibroblasts. Contact-inhibited 3T3 cells contain two forms of the enzyme, one with a K(m) of 2.5 μM and the second with a K(m) of 71 μM. As 3T3 cells grow to confluency and cAMP concentrations rise, the activity of the first enzyme increases, whereas that of the second is unchanged. A line of SV40-transformed 3T3 cells with low cAMP concentration also has low levels of the cAMP-phosphodiesterase with a K(m) of 2.5 μM. Treatment of 3T3 and SV40-transformed 3T3 cells with dibutyryl cAMP and theophylline increases cAMP-phosphodiesterase accumulation. This accumulation is blocked by cycloheximide and actinomycin D. The newly formed enzyme resembles the higher affinity enzyme present in unstimulated cells, since it has a K(m) of 1.2-2.0 μM, and is stimulated by snake venom. In L cells in which cAMP concentrations are elevated by treatment with prostaglandin E(1), cAMP phosphodiesterase also accumulates. We conclude that intracellular concentrations of cAMP regulate the synthesis of cAMP-phosphodiesterase, and that cAMP functions as an inducer of the enzyme.